Transitioning to Strong Partnerships for the Sustainable Development Goals - von Schnurbein , Georg (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Transitioning to Strong Partnerships for the Sustainable Development Goals is an edited volume dedicated to current developments regarding SDG 17 "Partnerships for the Goals". This goal contains preconditions and systemic issues that will facilitate the success of the SDGs in general. Thus, the volume covers conditions, structures, and means to strengthen the SDGs from both the theoretical and practical perspective. Transitioning to Strong Partnerships for the Sustainable Development Goals has three main focal points: Theoretical approaches to sustainable partnerships, including public-private partnerships. Different structural aspects for sustainable partnerships, including financial deals with philanthropic initiatives and new financing models as well as new technologies to meet the logistical challenges of development aid. Systemic issues, especially institutional coherence, multi-stakeholder approaches, and challenges of statistics for development. The invited academic and practical contributions cover a variety of different fields of research and expertise.